2020
DOI: 10.1039/d0cp04109b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying reversible nitrogenous ligand binding to Co(ii) porphyrin receptors at the solution/solid interface and in solution

Abstract: Single molecule microscopy can quantifiably probe the dynamics of reversible ligand binding to metalloporphyrin receptors at the solution/solid interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…However, we have shown (1) surface reactions can proceed orders of magnitude slower than expected based on solution phase kinetic measurement and (2) it is possible to correct rate constants for the effects of missed dwells due to low temporal resolution, thereby extending the range of rates that can be measured. Lest one assume that the O 2 -CoOEP/HOPG system is unique; we have tracked adsorption and desorption events in time for several systems including 1-phenylimidazole−CoOEP/HOPG, 38 4-methoxypyridine−CoOEP/ HOPG, 39 and imidazole−NiOEP/HOPG. 17 Thus, these systems are excellent candidates for stochastic analysis, and that work is underway.…”
Section: Table 1 Results Of Dwell Time Analysismentioning
confidence: 99%
“…However, we have shown (1) surface reactions can proceed orders of magnitude slower than expected based on solution phase kinetic measurement and (2) it is possible to correct rate constants for the effects of missed dwells due to low temporal resolution, thereby extending the range of rates that can be measured. Lest one assume that the O 2 -CoOEP/HOPG system is unique; we have tracked adsorption and desorption events in time for several systems including 1-phenylimidazole−CoOEP/HOPG, 38 4-methoxypyridine−CoOEP/ HOPG, 39 and imidazole−NiOEP/HOPG. 17 Thus, these systems are excellent candidates for stochastic analysis, and that work is underway.…”
Section: Table 1 Results Of Dwell Time Analysismentioning
confidence: 99%
“…The π–π structure seen in Figure c is significantly different from metal bonded ligands we have previously studied. To ascertain the role of the crown configuration of the ethyl groups in stabilizing the π–π structure, we also performed PW-DFT calculations on the PhThCoP-HOPG system. This allows us to ascertain the importance of the eight ethyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several STM studies reported by us and others have effectively demonstrated in situ chemistry and reaction dynamics of heterocyclic ligand coordination to metal complexes (porphyrins and phthalocyanines , ) adsorbed on solid supports at the solution/solid interface. Some of these reports confirmed that axial ligation can be reversible, and, furthermore, that the electronic properties, reactivity, and cooperativity (nonadditive interactions) of the adsorbed complex can be modulated by the underlying substrate. The binding reactions of imidazole to NiOEP and 1-phenylimidazole (PhIm) to CoOEP proceeded at room temperature because of charge donation from the underlying graphite substrate to porphyrin . The presence of highly ordered pyrolytic graphite (HOPG) was also crucial to observe positive cooperativity for both 4-methoxypyridine and PhIm binding to CoOEP at the solution/solid interface.…”
Section: Introductionmentioning
confidence: 89%
“…Not only do the molecules adsorb on the surface (molecule–surface interactions), but they also do so in a highly nonrandom and programmed fashion by achieving supramolecular interactions between themselves (molecule–molecule interactions). While the Langmuir adsorption isotherm holds true for the self-assembly of several systems such as in the cases of small molecule binding on metalloporphyrins, , the assumption of noninteracting molecules makes it unsuitable for application to systems where molecules interact. Clearly, this simplest analytical thermodynamic model fails to explain experimentally observed behavior in the studied ISA systems.…”
Section: Discussionmentioning
confidence: 99%
“…The adapted Born–Haber cycle approach combines experimental results with computations to derive the enthalpy change upon self-assembly for hydrogen- and halogen-bonded systems, while the entropic contributions are mainly calculated based on statistical mechanics. ,, Additionally, the same group expanded the possibilities for studying these systems by STM with the development of an immersion-type STM that has, among other things, allowed the quantitative study of ultraslow kinetic processes at the liquid/solid interface. , Hipps et al have mainly focused on the investigations of porphyrin systems. They have been able to compare ligand binding in solution to on-surface binding, observed cooperative effects in ligand binding to the porphyrin monolayers, and successfully evaluated thermodynamic parameters for several systems. In a recent publication, Hipps et al reported a detailed study exploring the effects of solvent on the structure, stability, and dynamics of a physisorbed porphyrin SAMN. They have additionally been able to use STM to observe and monitor the initial stages of adlayer formation and growth, which provided insight into the mechanism and rates of self-assembly on surfaces …”
Section: Introductionmentioning
confidence: 99%